Organizational and economic problems of the technical and technological providing of grain production Организационно-экономические проблемы технико-технологического обеспечения зернопроизводства - Khristenko Galina M. (Bìznes Inform, 2012)
The organizational and economic problems of the technical and technological providing of grain production are reflected. The modern state of material hardware of the grain production of the Ternopil region is analyzed. Innovative directions of development of technologies of grain production are certain and them hardware in a region. Отражены организационно-экономические проблемы технико-технологического обеспечения зернопроизводства. Проанализировано современное состояние материально-технического обеспечения зернового хозяйства Тернопольской области. Определены инновационные направления развития технологий зернопроизводства и их технического обеспечения в регионе.